A Comprehensive Systematic Review of Plant Species Utilized for Dental Care Management in Himachal Pradesh, India - Suman, Rawat; Surbhi; Dhatwalia, Sunil Kumar (Ethnobotany Research and Applications, 2024)
Background: Mouth is a mirror that reflects the health of our body. There is a connection between oral health and other health systems of our body. Oral diseases and mouth disorders affect individuals of all age groups. These include bad breath, ulcers, pyorrhea, dental caries, gingivitis, edentulism, oral cancer, etc. There is an increasing demand of herbal remedies for toothcare nowadays. This paper offers a concise overview of research conducted on the utilization of plant resources for dental hygiene maintenance in Himachal Pradesh. Methods: An extensive survey of literature was carried out by retrieving and screening a number of articles from various sources. Only relevant articles were selected and studied thoroughly. Results: About 90 plant species which belong to 55 families are enumerated, of which Lamiaceae family is used most frequently with six species. Mostly, leaf parts are used to treat oral problems. 23 plant species are used as tooth powder or brushing sticks. Many plant species are used to cure oral problems like toothache (38 species), mouth ulcers (13 species), mouth sores (eight species), pyorrhea (four species), gum inflammation (two species) and mouth blisters (two species). Conclusions: A number of plant species have been used since ages for toothcare management in Himachal Pradesh. These are economical, safe and have numerous benefits. Keywords: Dental hygiene; Toothache; Oral health; Pyorrhea